Abnormal growth in super-low supersaturation microchannel epitaxy of (001) GaAs and its improvement. (13th January 2015) - Tomita, Masafumi; Takakura, Hiroyuki; Kambayashi, Daisuke; Mizuno, Yosuke; Naritsuka, Shigeya; Maruyama, Takahiro
Abstract: Microchannel epitaxy (MCE) of (001) GaAs with super-low supersaturation usually provides a very thin and wide lateral growth. However, it sometimes produces abnormal growth with a very low aspect ratio. In the abnormal growth, the layer grows very thick, and accordingly, the width becomes small. The aspect ratio is less than 1. The cause of the abnormal growth is studied and the edge effect is found to be responsible. The edge effect in liquid phase epitaxy (LPE) produces a high supersaturation near the periphery. Consequently, numerous steps are produced on the surface of the edge. This forms a step source in LPE and grows a thick layer with a very low aspect ratio. To suppress the abnormal growth, two types of mask patterns are proposed, which are designed to decrease supersaturation at the periphery. With the aid of the new masks, very wide and thin MCE layers are successfully obtained with high yields. For example, the width and thickness of an MCE layer are 210 and 6 µm, respectively, giving a high aspect ratio of 35.